Social Media and the Transformation of Lifestyle Patterns among Generation Z: Evidence and Implications from Cibubur Raya, Indonesia - Muhammad Shafiy Deedat Rifai; Siti Mukaromah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Generation Z (Gen Z), born between approximately 1995 and 2010, is the first generation to grow up fully embedded in digital ecosystems and social media environments. In Indonesia, particularly in semi-urban areas such as Cibubur Raya, the widespread use of smartphones and app-based platforms has profoundly reshaped daily routines, consumption patterns, social interactions, and value orientations among Gen Z students. This article examines how social media use influences Gen Z lifestyles in Cibubur Raya, focusing on mobility, consumption behaviour, health-related practices, and socio-emotional life. Using a mixed-methods explanatory–descriptive approach, the study integrates a narrative review of global and Indonesian research published between 2020 and 2025, a conceptual synthesis of generational and social network theories, and the design of a school-based survey complemented by qualitative insights from teachers. Validated measurement instruments on social media use and problematic use among adolescents inform the survey framework. The findings identify four key patterns. First, high levels of social media engagement support identity formation and peer belonging but also contribute to social fatigue and problematic use for some adolescents. Second, influencer cultures significantly shape consumption, mobility, and financial behaviours, generating both opportunities and risks. Third, intensive social media use is associated with sleep disruption, sedentary lifestyles, body image concerns, and mental health symptoms, though impacts vary by context. Fourth, teachers observe a gap between students’ digital skills and their critical literacy, ethical awareness, and resilience. The study concludes by recommending integrated digital literacy, health, and well-being interventions.